Penerapan Komunikasi Terapeutik Pada Pasien Perilaku Kekerasan - Resman Humolungo (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: Violent behaviour is a form of behaviour that patients with schizophrenia can demonstrate. This behaviour can cause injury to the patient or others around him. Therapeutic communication applied by nurses becomes one of the intervention options for patients with violent behaviour. Objective: Knowing the application of therapeutic communication in violent behaviour patients. Methods: Qualitative research with phenomenology case study approach method. Result: Shows that patient I have more contact with others. With an attitude that shows violent behaviour that can threaten people around him compared to patient II, who rarely meets others. Conclusion: Therapeutic communication has a very strong relationship with the decreased risk of violent behaviour in patients with violent behaviour. The better the communication the nurse applies, the lower the risk of violent behaviour appearing